35.4k views
5 votes
Can you solve m²-3m-10=0, THANKS

2 Answers

4 votes

Answer:

m = - 2, m = 5

Explanation:

Given

m² - 3m - 10 = 0

Consider the factors of the constant term (- 10) which sum to give the coefficient of the m- term (- 3)

The factors are - 5 and + 2, since

- 5 × 2 = - 10 and - 5 + 2 = - 3, hence

(m - 5)(m + 2) = 0

Equate each factor to zero and solve for m

m + 2 = 0 ⇒ m = - 2

m - 5 = 0 ⇒ m = 5

User Max Martynov
by
4.6k points
2 votes

Answer:


m_(1) =5\\\\m_(2) =-2

Explanation:

using quadratic formula:


m = \frac{-b+-\sqrt{b^(2)-4*a*c}}{2*a}

in this case:

a = 1 b= -3 c= -10

we have:


m =\frac{-(-3)+-\sqrt{(-3)^(2)-4*1*-10}}{2*1}\\\\m =(3+-√(9+40))/(2)\\\\m = (3+-√(9+40))/(2)\\ \\m =(3+-√(49))/(2)\\\\m_(1) = (3+7)/(2) =5\\\\m_(2) = (3-7)/(2) = -2

User Charles Ritchie
by
4.6k points